KADAR PROTEIN, SUSUT MASAK DAN ORGANOLEPTIK RENDANG KHAS-PIDIE YANG DIBERI PENAMBAHAN BAWANG PUTIH (Allium sativum) PADA KONSENTRASI YANG BERBEDA - Masyitah; Amhar Abubakar (LPPM Universitas Terbuka, 2023)
Rendang is one of the traditional cuisines from Sumatera. It is made from beef that has been cooked for hours and mixed with various seasonings and spices to produce a quality product. One of natural ingredients that can be used to preserve meat product is garlic (Allium sativum). This research aimed to study the effect of different concentrations of garlic on the protein content, cooking loss, and organoleptic qualities (color, aroma, taste, texture) of Pidie rendang. The research design used a completely randomized design (CRD) of 4 treatments (0%, 5%, 10%, 15%) with 5 replications. The observed variables were protein content, cooking loss, and organoleptic quality. The ANOVA results showed that the addition of garlic significantly affected (P<0,01) the protein content, but did not affect the cooking loss and organoleptic quality parameters. It can be concluded that garlic concentration is positively related to the protein content of rendang. The highest protein content was found in the 15 % garlic concentration treatment, reaching up to 17,11%.